Scaling Thermal Properties from the Leaf to the Canopy in the Alaskan Arctic Tundra. Issue 4 (1st November 2016) - Gersony, Jessica T.; Prager, Case M.; Boelman, Natalie T.; Eitel, Jan U. H.; Gough, Laura; Greaves, Heather E.; Griffin, Kevin L.; Magney, Troy S.; Sweet, Shannan K.; Vierling, Lee A.; Naeem, Shahid
ABSTRACT: Plants are strongly influenced by their thermal environments, and this influence manifests itself in a variety of ways, such as altered ranges, growth, morphology, or physiology. However, plants also modify their local thermal environments through feedbacks related to properties and processes such as albedo and evapotranspiration. Here, we used leaf- and plot- level thermography on the north slope of the Brooks Range, Alaska, to explore interspecific differences in thermal properties among arctic tundra plants, and to determine if species differentially contribute to plot temperature. At the leaf-level, we found significant differences ( p < 0.05) for in situ temperatures among the 13 study species. At the plot level, we found that the fractional cover of vascular plant species, lichen, litter, and moss had a significant effect on plot temperature ( p < 0.05, R 2 = 0.61). A second model incorporating thermal leaf properties—in addition to the fraction of vascular plant and other dominant ground covers—also predicted plot temperature, but with lower explanatory power ( p < 0.05, R 2 = 0.32). These results potentially have important implications for our understanding of how individual plant species influence canopy-level thermal properties and how temperature—dependent properties and processes may be impacted by climate change—induced shifts in species composition.